Globalisation's impact on the Global Public Goods & Public Bad: An Economics view on the EBOLA outbreak - Ahir, Vijay J. (International Journal of Scientific Research and Management (IJSRM), 2015)
A trend called globalization, which started at the early onset of this century, has increased interdependency amonginternational nations. This interdependency has both negative as well as positive effects. An increased air travelnetwork has contributed significantly in global trade. Public goods such as Internet, Financial stability, commercialintegration or knowledge promotion has created a new category, which is known as International public goods.Global interdependence has generated few negative effects as well. Increased international mobility has increasedthe risk of contagion in case of deadly diseases. We have witnessed many International Public Bad, which issymmetry to public goods, such as spread of H1N1, Influenza, in the past.